Sea urchin-shaped titanium niobate electrode material and preparation method thereof

Preparation of sea urchin-shaped titanium niobate electrode material through one-step hydrothermal synthesis method has solved the shortcomings of existing lithium-ion battery materials in terms of safety and electrochemical performance, achieved high magnification and long cycle stability, and is suitable for use in lithium-ion batteries. Negative electrode material.

CN119263347APending Publication Date: 2025-01-07NANYANG NORMAL UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411616734.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-13
Publication Date
2025-01-07

AI Technical Summary

Technical Problem

Existing lithium-ion battery anode materials have shortcomings in terms of safety, fast charging performance and cycle stability. In particular, the low electronic and ionic conductivity of titanium niobate materials leads to poor magnification and cycle performance, which hinders its commercial application. .

Method used

A one-step hydrothermal synthesis method was used to prepare a titanium niobate electrode material with regular sea urchin morphology. By adjusting the concentration of niobium ion, the volume ratio of alcohol to deionized water and the molar ratio of fluoride ion, the morphology and size of the material were controlled to form 2-5 micron structure assembled from 40 nm titanium niobate nanorods.

Benefits of technology

The prepared sea urchin-like titanium niobate material exhibits excellent electrochemical properties, including high magnification and long cycle stability, with discharge specific capacity of 216 mAh/g and 175 mAh/g at 10C and 30C respectively, and the process is simple. , suitable for large-scale industrial production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

The invention discloses a preparation method of a sea urchin-shaped titanium niobate electrode material. The preparation method comprises the following steps: dissolving niobium pentachloride in a mixed solution of deionized water and alcohol; and adding a titanium source and a proper amount of hydrofluoric acid, filling the obtained mixed solution into a reaction kettle for heating reaction, cooling, washing, drying and calcining to obtain the sea urchin-shaped titanium niobate electrode material. The electrode material disclosed by the invention has a regular urchin-shaped structure and good dispersity, and shows excellent electrochemical performance when being used as a lithium ion battery negative electrode material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of lithium ion battery materials, and in particular relates to a sea urchin-shaped titanium niobate electrode material and a preparation method thereof. Background Art

[0002] Lithium-ion batteries are used as the main power source for electric vehicles due to their excellent performance. With the rapid development of the electric vehicle industry, people have higher and higher requirements for the cruising range and fast charging performance of electric vehicles, which puts higher requirements on the performance of lithium-ion batteries, including safety, fast charging and service life. The currently widely used graphite carbon negative electrode material can no longer meet the above requirements. Although lithium titanate has high safety, excellent cycle stability and fast charging performance as a lithium-ion negative electrode material, its low theoretical specific capacity reduces the energy density of the battery, which in turn hinders its application in power batteries. Therefore, it is urgent to develop new lithium-ion battery negative electrode materials with high safety and high rate performance.

[0003] Titanium niobate (TiNb2O7) has a high lithium insertion / extraction potential (about 1.65 V), which avoids the formation of lithium dendrites and improves the safety of the battery; three redox reaction pairs participate in the lithium insertion / extraction process, which gives it a high theoretical specific capacity (388 mAh / g). In addition, the material has a shear plane ReO3 type crystal structure and has excellent cycle stability. Therefore, titanium niobate is a promising high-performance negative electrode material for lithium-ion power batteries. However, due to the low electronic and ionic conductivity of titanium niobate, its rate and cycle performance are poor, resulting in unsatisfactory electrochemical performance, which in turn restricts its commercial application.

[0004] People have taken a variety of approaches to improve the electrochemical performance of titanium niobate, such as element doping, carbon-based material coating, construction of oxygen defects or reducing particle size. Reducing the particle size can shorten the transmission distance of electrons and lithium ions and enhance the electrochemical reaction kinetics of electrode materials. People have synthesized a variety of low-dimensional titanium niobate materials, such as nanoparticles, nanowires, nanosheets, nanorods, etc., which show good electrochemical performance. However, the high surface energy of nanostructured electrode materials can induce adverse side reactions, and the adhesion to the fluid is weak, which hinders their practical application. Studies have found that constructing a three-dimensional structure system with a scale of microns composed of low-dimensional nanostructured materials has the advantages of both nano and micro electrode materials, which can shorten the diffusion path of lithium ions and electrons and enhance the cycle stability of electrode materials. So far, except for titanium niobate mesoporous microspheres composed of nanoparticles, there are few reports on micro-nanostructured titanium niobate materials with other morphological structures. Although Zhao et al. claimed to have synthesized sea urchin-like titanium niobate materials by spray drying, their morphology is more like an unopened flower, and the morphology is irregular and uneven (H. Zhao, Y. Ren, S. Chen, J. Xu, Z. Lu, Novel synthesis of sea urchins-like TiNb2O7 with hierarchical structure as anode for lithium-ion batteries, Materials Letters 284 (2021) 128950). Therefore, it is urgent to explore new methods for preparing micro-nanostructured titanium niobate electrode materials.

[0005] Based on this, this application was developed. Summary of the invention

[0006] The present invention aims to overcome the defects of the prior art and provide a sea urchin-shaped titanium niobate electrode material. The electrode material has a regular sea urchin-shaped morphology and good dispersibility, and exhibits excellent electrochemical properties when used as a negative electrode material for lithium-ion batteries.

[0007] The present invention also provides a method for preparing the sea urchin-shaped titanium niobate electrode material.

[0008] To achieve the above object, the present invention adopts the following technical solution: A method for preparing a sea urchin-shaped titanium niobate electrode material, wherein the preparation of the sea urchin-shaped titanium niobate electrode material comprises the following steps: Step 1) dissolving niobium pentachloride in a mixture of deionized water and alcohol to obtain a niobium solution; Step 2) adding the corresponding titanium source according to the titanium / niobium atomic ratio of 0.4-0.6:1 and stirring for 0.1-6 hours; Step 3) adding a certain amount of hydrofluoric acid to the mixed solution obtained in step 2) and continuing the reaction for 0.1-36 hours; Step 4) heating the mixed solution obtained in step 3) to react for a certain period of time; washing, drying and calcining the obtained reaction precipitate to obtain a sea urchin-shaped titanium niobate electrode material; the sea urchin-shaped titanium niobate prepared by this method has a regular morphology and structure, and has good dispersibility, and exhibits excellent electrochemical properties when used as a negative electrode material for lithium-ion batteries.

[0009] Specifically, when preparing the sea urchin-shaped titanium niobate electrode material, the concentration of niobium ions in step 1) is 0.001-30 mol / L; the alcohol includes but is not limited to one or more of ethanol, isopropanol, methanol, ethylene glycol, n-butanol, glycerol, diethylene glycol, n-propanol, etc.; the volume ratio of alcohol to deionized water is 0.1-20:1 (i.e., 1:10-20:1), and more preferably 1:5-10:3.

[0010] Specifically, when preparing the sea urchin-shaped titanium niobate electrode material, in step 2), the titanium source includes but is not limited to one or more of titanium isopropoxide, isopropyl titanate, and tetrabutyl titanate; in step 3), the molar ratio of niobium ions to fluoride ions is 1: 0.1-60, more preferably 1: 0.25-1.40. Hydrofluoric acid is a morphology regulator.

[0011] Specifically, when preparing the sea urchin-shaped titanium niobate electrode material, in step 4), the reaction is heated at 110-260°C for 0.5-60 hours; and calcined at 300-1200°C for 0.5-70 hours. More preferably, the reaction is heated at 120-210°C for 15-48 hours; and calcined at 550-1000°C for 3-60 hours. Drying is vacuum drying at a temperature of 60-120°C for 1-24 hours.

[0012] The present invention provides a sea urchin-shaped titanium niobate electrode material prepared by the above-mentioned preparation method. The sea urchin-shaped titanium niobate material is formed by assembling titanium niobate nanorods with a size of about 40 nanometers, and the size of the titanium niobate material is about 2-5 microns. The prepared sea urchin-shaped titanium niobate material is used as a negative electrode material for lithium-ion batteries and exhibits excellent rate and cycle stability.

[0013] The present invention also provides the use of the sea urchin-shaped titanium niobate electrode material as a negative electrode material in a lithium ion battery.

[0014] Compared with the prior art, the present invention has the following advantages and beneficial effects: 1) The present invention prepares a sea urchin-like titanium niobate material for the first time. The prepared sea urchin-like titanium niobate material not only has a regular sea urchin-like morphology, but also has good dispersibility.

[0015] 2) The sea urchin-shaped titanium niobate material prepared by the present invention is formed by one-dimensional nanowires (size of about 40 nanometers) with an overall size of about 2-5 micrometers. It has the advantages of both nano and micro materials and exhibits excellent electrochemical performance when used as a negative electrode for lithium-ion batteries: the discharge specific capacity at 10C and 30C rates is 216 mAh / g and 175 mAh / g, respectively.

[0016] 3) The present invention can also control the morphology and size of the product by adjusting the molar ratio of niobium ions to fluoride ions, the volume ratio of alcohol to deionized water, etc.

[0017] 4) The method of the present invention only requires one step of hydrothermal synthesis, the synthesis process is simple, the reaction is highly controllable, and it is easy to be mass-produced industrially.

[0018] Of course, any product implementing this application does not necessarily need to achieve all of the technical effects described above at the same time. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] The drawings described herein are used to provide a further understanding of the present invention and constitute a part of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the drawings: Figure 1 is an X-ray diffraction (XRD) diagram of a sea urchin-shaped titanium niobate material prepared in Example 1 of the present invention; Figure 2 is a scanning electron microscope (SEM) photograph of the sea urchin-shaped titanium niobate material prepared in Example 1 of the present invention; Figure 3 This is a transmission electron microscope (TEM) photograph of the sea urchin-shaped titanium niobate material prepared in Example 1 of the present invention; Figure 4 It is a scanning electron microscope image of the sea urchin-shaped titanium niobate material prepared in Example 1 of the present invention and a surface distribution map of titanium (Ti), niobium (Nb) and oxygen (O) elements; Figure 5 1 is a charge-discharge curve diagram of the sea urchin-shaped titanium niobate material prepared in Example 1 of the present invention at different rates (1C=388 mAh / g); Figure 6 This is a long cycle performance curve of the sea urchin-shaped titanium niobate material prepared in Example 1 of the present invention at a 10C rate. DETAILED DESCRIPTION

[0020] The technical solution of the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments, but the protection scope of the present invention is not limited thereto.

[0021] In the following examples, the raw materials used are all common commercial products that can be directly purchased or can be prepared by conventional methods in the art.

[0022] Example 1 Step 1) adding niobium pentachloride to a mixture of deionized water and ethanol, stirring until clarified, to obtain a niobium solution, wherein the concentration of niobium ions is 0.59 mol / L, and the volume ratio of ethanol to deionized water is 1:2; Step 2) Weigh the corresponding titanium isopropoxide according to the titanium / niobium atomic ratio of 0.52 and add it to the above solution, stirring for 3 hours; Step 3) adding hydrofluoric acid to the mixed solution obtained in step 2), wherein the molar ratio of niobium ions to fluoride ions is 1:2.1, and continuing stirring to react for 10 hours; Step 4) transferring the mixed solution obtained in step 3) into a stainless steel reactor, placing it in a forced air drying oven at 150° C. for reaction for 48 hours; Step 5) The reaction precipitate obtained in step 4) is washed with deionized water and ethanol for several times, and then placed in a drying oven at 80° C. for 2 hours under vacuum; Step 6) The powder obtained in step 5) is placed in a muffle furnace and calcined at 850° C. for 24 hours to obtain a sea urchin-shaped titanium niobate material.

[0023] Figure 1 The X-ray diffraction pattern of the sea urchin-shaped titanium niobate material prepared in Example 1 is given. Figure 1 As shown, the diffraction peaks of the sample are completely consistent with the diffraction peaks of titanium niobate in the standard PDF card, and no other impurity peaks are found, indicating that the synthesized sea urchin-shaped titanium niobate material has a high purity.

[0024] Figure 2 The scanning electron microscope (SEM) photo of the sea urchin-shaped titanium niobate material prepared in Example 1 is given. Figure 2 As shown, the sample has a regular sea urchin-like morphology, a size of about 2-5 μm, and good dispersibility.

[0025] Figure 3 The transmission electron microscope (TEM) photo of the sea urchin-shaped titanium niobate material prepared in Example 1 is given. Figure 3 As shown, it is further proved that the sample has a sea urchin-like morphology, and the size of the nanorods of titanium niobate that make up the sea urchin-like shape is about 40 nanometers.

[0026] Figure 4 The element surface distribution diagram (EDS) of the sea urchin-shaped titanium niobate material prepared in Example 1 is given. Figure 4 As shown, the Ti, Nb and O elements are evenly distributed in the sample, further proving that the synthesized material is a sea urchin-like titanium niobate material.

[0027] The prepared sea urchin-shaped titanium niobate material, carbon black and polyvinylidene fluoride were ground and mixed in a mass ratio of 7:2:1, and a certain amount of N-methylpyrrolidone was added and stirred for 6 hours to prepare a uniform slurry. The prepared slurry was evenly coated on the copper foil with a coater and baked in a vacuum drying oven at 120 °C for 12 hours. The baked electrode was punched into a φ12 mm disc with a punching machine and compacted with a pressure of 6-8 MPa. In a glove box filled with argon, a metal lithium sheet was used as the counter electrode, a polypropylene fiber was used as the diaphragm, and 1 mol L -1 LiPF6 / EC+DMC (volume ratio 1:1) was used as the electrolyte to assemble CR2025 button cells. The assembled cells were left to stand for 12 h before the electrochemical performance test was performed on the battery test system.

[0028] Figure 5 The charge and discharge curves of the sea urchin-shaped titanium niobate material prepared in Example 1 at different rates are given (1C=388 mAh / g). Figure 5 As shown, the urchin-shaped titanium niobate has excellent rate performance as a negative electrode material for lithium-ion batteries, with capacities of 272, 233, 216, 193 and 175 mAh / g at 1, 5, 10, 20 and 30 C rates, respectively.

[0029] Figure 6 The long cycle performance curve of the sea urchin-shaped titanium niobate material prepared in Example 1 at a rate of 10C is given. Figure 6 As shown, the capacity of the urchin-shaped titanium niobate material as a negative electrode material for lithium-ion batteries remains at 142 mAh / g after 500 cycles at a 10C rate.

[0030] Example 2 Step 1) adding niobium pentachloride to a mixture of deionized water and isopropanol, stirring until clarified, to obtain a niobium solution, wherein the concentration of niobium ions is 1.35 mol / L, and the volume ratio of isopropanol to deionized water is 10:3; Step 2) Weigh the corresponding tetrabutyl titanate according to the titanium / niobium atomic ratio = 0.49 and add it to the above solution, stirring for 4.5 hours; Step 3) adding hydrofluoric acid to the mixed solution obtained in step 2), wherein the molar ratio of niobium ion to fluoride ion is 1:0.82, and continuing stirring to react for 5 hours; Step 4) transferring the mixed solution obtained in step 3) into a stainless steel reactor, placing it in a forced air drying oven at 210° C. for 16 hours; Step 5) The reaction precipitate obtained in step 4) is washed with deionized water and ethanol for several times, and then placed in a drying oven at 70° C. for 8 hours under vacuum; Step 6) The powder obtained in step 5) is placed in a muffle furnace and calcined at 910° C. for 10 hours to obtain a sea urchin-shaped titanium niobate material.

[0031] Example 3 Step 1) adding niobium pentachloride to a mixture of deionized water and ethylene glycol, stirring until clarified, to obtain a niobium solution, wherein the concentration of niobium ions is 0.82 mol / L, and the volume ratio of ethylene glycol to deionized water is 1:3; Step 2) Weigh the corresponding tetrabutyl titanate according to the titanium / niobium atomic ratio = 0.53 and add it to the above solution, stirring for 3 hours; Step 3) adding hydrofluoric acid to the mixed solution obtained in step 2), wherein the molar ratio of niobium ions to fluoride ions is 1:20, and continuing stirring to react for 2 hours; Step 4) transferring the mixed solution obtained in step 3) into a stainless steel reactor, placing it in a forced air drying oven at 172° C. for reaction for 20 hours; Step 5) The reaction precipitate obtained in step 4) is washed with deionized water and ethanol for several times, and then placed in a drying oven at 75° C. and vacuum dried for 12 hours; Step 6) The powder obtained in step 5) is placed in a muffle furnace and calcined at 790° C. for 60 hours to obtain a sea urchin-shaped titanium niobate material.

[0032] Example 4 Step 1) adding niobium pentachloride to a mixture of deionized water and ethanol, stirring until clarified, to obtain a niobium solution, wherein the concentration of niobium ions is 20 mol / L, and the volume ratio of ethanol to deionized water is 2:5; Step 2) Weigh the corresponding titanium isopropoxide according to the titanium / niobium atomic ratio of 0.50 and add it to the above solution, stirring for 2 hours; Step 3) adding hydrofluoric acid to the mixed solution obtained in step 2), wherein the molar ratio of niobium ions to fluoride ions is 1:6.2, and continuing to stir and react for 36 hours; Step 4) transferring the mixed solution obtained in step 3) into a stainless steel reactor, placing it in a forced air drying oven at 209° C. for reaction for 51 hours; Step 5) The reaction precipitate obtained in step 4) is washed with deionized water and ethanol for several times, and then placed in a drying oven at 75° C. and vacuum dried for 20 hours; Step 6) The powder obtained in step 5) is placed in a muffle furnace and calcined at 862° C. for 31 hours to obtain a sea urchin-shaped titanium niobate material.

[0033] Example 5 Step 1) adding niobium pentachloride to a mixture of deionized water and methanol, stirring until clarified, to obtain a niobium solution, wherein the concentration of niobium ions is 15.3 mol / L, and the volume ratio of methanol to deionized water is 1:1; Step 2) Weigh the corresponding tetrabutyl titanate according to the titanium / niobium atomic ratio of 0.51 and add it to the above solution, stirring for 8 hours; Step 3) adding hydrofluoric acid to the mixed solution obtained in step 2), wherein the molar ratio of niobium ions to fluoride ions is 1:12, and continuing to stir and react for 12 hours; Step 4) transferring the mixed solution obtained in step 3) into a stainless steel reactor, placing it in a forced air drying oven at 160° C. for reaction for 38 hours; Step 5) The reaction precipitate obtained in step 4) is washed with deionized water and ethanol for several times, and then placed in a drying oven at 85° C. for 3 hours under vacuum; Step 6) The powder obtained in step 5) is placed in a muffle furnace and calcined at 950° C. for 3 hours to obtain a sea urchin-shaped titanium niobate material.

[0034] Under the same conditions, the charge and discharge performance at different rates and the long cycle performance at a rate of 10C of the sea urchin-shaped titanium niobate materials prepared in Examples 2 to 5 were tested. The results showed that the prepared sea urchin-shaped titanium niobate materials had electrochemical properties comparable to those of Example 1.

[0035] It should also be noted that the terms "include", "comprises" or any other variations thereof are intended to cover non-exclusive inclusion, so that a product or system including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such a product or system. In the absence of more restrictions, the elements defined by the sentence "comprises a ..." do not exclude the existence of other identical elements in the product or system including the elements.

[0036] The above description shows and describes several preferred embodiments of the present invention, but as mentioned above, it should be understood that the present invention is not limited to the form disclosed herein, and should not be regarded as excluding other embodiments, but can be used in various other combinations, modifications and environments, and can be modified within the scope of the invention concept described herein through the above teachings or the technology or knowledge of the relevant field. Changes and variations made by those skilled in the art do not depart from the spirit and scope of the present invention, and should be within the scope of protection of the claims attached to the present invention.

Claims

1. A method for preparing a sea urchin-shaped titanium niobate electrode material, characterized in that: The preparation of the sea urchin-shaped titanium niobate electrode material comprises the following steps: Step 1) dissolving niobium pentachloride in a mixture of deionized water and alcohol to obtain a niobium solution; Step 2) adding the corresponding titanium source according to the titanium / niobium atomic ratio of 0.4-0.6:1 and stirring for 0.1-6 hours; Step 3) adding a certain amount of hydrofluoric acid to the mixed solution obtained in step 2) and continuing the reaction for 0.1-36 hours; Step 4) heating the mixed solution obtained in step 3) to react for a certain period of time; washing, drying and calcining the reaction precipitate to obtain the sea urchin-shaped titanium niobate electrode material.

2. The preparation method according to claim 1, characterized in that: In step 1), the concentration of niobium ions is 0.001-30 mol / L.

3. The preparation method according to claim 1, characterized in that: In step 1), the volume ratio of alcohol to deionized water is 0.1-20: 1; the alcohol includes one or more of ethanol, isopropanol, methanol, ethylene glycol, n-butanol, glycerol, diethylene glycol, and n-propanol.

4. The preparation method according to claim 1, characterized in that: The titanium source in step 2) is one or more of titanium isopropoxide, isopropyl titanate, and tetrabutyl titanate.

5. The preparation method according to claim 1, characterized in that: In step 3), the molar ratio of niobium ions to fluorine ions is 1: 0.1-60.

6. The preparation method according to claim 1, characterized in that: In step 4), the reaction is heated at 110-260° C. for 0.5-60 hours; and calcined at 300-1200° C. for 0.5-70 hours.

7. A sea urchin-shaped titanium niobate electrode material prepared by the preparation method according to any one of claims 1 to 6.

8. Use of the sea urchin-shaped titanium niobate electrode material according to claim 7 as a negative electrode material in a lithium-ion battery.